Predictive value of cardiovascular risk factors in the formation of cardiovascular and all-cause mortality: results of a 27-year cohort prospective study - I. V. Dolgalev; A. Yu. Ivanova; R. S. Karpov (Российский кардиологический журнал, 2023)
Aim. To study the prognostic significance of cardiovascular risk factors (RFs) in the formation of all-cause and cardiovascular mortality based on the results of a 27-year prospective cohort study of Tomsk population of both sexes aged 20-59 years.Material and methods. The object of study was random house-to-house sample of Tomsk population. In total, 1546 people (630 men and 916 women) aged 20-59 were examined. In 1988-1991, the prevalence of following cardiovascular RFs was studied: hypertension (HTN), overweight, smoking, alcohol consumption, hypercholesterolemia (HCE), low high-density lipoprotein cholesterol levels (hypo-HDL-emia), hypertriglyceridemia (HTG). All examination methods used were strictly standardized. To determine the RF, the criteria generally accepted in epidemiological studies were used. Over 27 years of follow-up, 330 deaths were recorded, including 142 due to cardiovascular disease.Results. In the multivariate Cox proportional hazard model, the following variables were studied: HTN, overweight, smoking, alcohol consumption, HCE, hypo-HDL-emia, HTG, coronary artery disease (CAD) (according to epidemiological criteria), and age. The strongest predictor of of all-cause death was frequent alcohol use (relative risk (RR) 2,75). Smoking increased the risk of death by 2,72 times. Among former smokers, the risk of all-cause death was 1,9 times higher compared to non-smokers. HTN increases the death risk by 1,61 times. Each year of life lived increases the death risk by 1,06 times. The most significant risk factor for death from CVD was frequent alcohol consumption (RR 3,01). Smoking increases the cardiovascular death risk by 2,28 times. Among former smokers, the RR of cardiovascular death was 1,91. HTN increases the risk of cardiovascular mortality by 1,84 times compared with people with normal blood pressure. Each year of life lived increases the risk of cardiovascular death by 1,1 times. In multivariate analysis, overweight, HCE, hypo-HDL-emia, HTG did not have a significant independent effect on the all-cause and cardiovascular death risk.Conclusion. In a 27-year cohort prospective study, independent predictors of all-cause and cardiovascular mortality, along with hypertension and age, were lifestyle risk factors, such as smoking and frequent alcohol consumption.